Reproducibility for isometric and isokinetic maximum knee flexion and extension measurements using the IsoMed 2000-dynamometer - Dirnberger, J.; Wiesinger, H.-P.; Kösters, A.; Müller, E. (Isokinetics and Exercise Science, 2012)
The present study was conducted to evaluate the relative and absolute reproducibility of the IsoMed 2000-dynamometer in measuring Peak Torque (PT) during maximum isometric and isokinetic (60 and 120°/s) knee flexion and extension. Thirty four physically active male subjects (mean age: 23.2 years) were measured in three sessions (T1-T3), 48-72 h apart. Repeated measures analysis of variance (ANOVA) with Bonferroni post hoc adjustments revealed significant systematic errors for isokinetic flexion measurements with mean values on the second and third visit being around 3-5% than the corresponding values obtained in the first visit. Intraclass correlation coefficients (ICC 2,1) of 0.90-0.98 and 0.94-0.98 combined with values of standard error of measurement (SEM) of 5.5-9.1 and 4.0-9.0 Nm were found for T1-T2 and T2-T3, respectively. Based on the systematic errors found for flexor measurements and a clear improvement in reproducibility parameters from T1-T2 to T2-T3 for nearly all measurements, we recommend the use of a familiarisation session prior to actual testing.